Thermoelectric properties of A-site deficient La-doped SrTiO3 at 100–900 °C under reducing conditions. Issue 2 (February 2020) - Singh, Sathya Prakash; Kanas, Nikola; Desissa, Temesgen D.; Johnsson, Mats; Einarsrud, Mari-Ann; Norby, Truls; Wiik, Kjell
Abstract: Lanthanum doped strontium titanate is a potential n-type thermoelectric material at moderate and high temperatures. (La0.12 Sr0.88 )0.95 TiO3 ceramics were prepared by two different routes, conventional sintering at 1500 °C and spark plasma sintering at temperatures between 925 and 1200 °C. Samples with grain size between 40 nm and 1.4 μm were prepared and characterized with respect to their thermoelectric transport properties at temperatures between 100 and 900 °C under reducing conditions (H2 /H2 O-buffer mixtures). The thermal conductivity was significantly reduced with decreasing grain size reaching a value of 1.3 W m −1.  K −1 at 600 °C for grain size of 40 nm and porosity of 19%. Electrical conductivity increased with increasing grain size showing a maximum of 500 S cm −1 at 200 °C for a grain size of 1.4 μm. The highest figure-of-merit ( zT ) was measured for samples with 1.4 μm average grain size reaching 0.2 at 500 °C.